Biological Significance of NOTCH Signaling Strength - Shen, Wei; Huang, Jiaxin; Wang, Yan (Frontiers in Cell and Developmental Biology, 2021)
The evolutionarily conserved NOTCH signaling displays pleotropic functions in almost every organ system with a simple signaling axis. Different from many other signaling pathways that can be amplified via kinase cascades, NOTCH signaling does not contain any intermediate to amplify signal. Thus, NOTCH signaling can be activated at distinct signaling strength levels, disruption of which leads to various developmental disorders. Here, we reviewed mechanisms establishing different NOTCH signaling strengths, developmental processes sensitive to NOTCH signaling strength perturbation, and transcriptional regulations influenced by NOTCH signaling strength changes. We hope this could add a new layer of diversity to explain the pleotropic functions of NOTCH signaling pathway.